2016
DOI: 10.1177/1687814016680143
|View full text |Cite
|
Sign up to set email alerts
|

Trajectories of coarse granular sediment particles in a simplified centrifugal dredge pump model

Abstract: Due to different inertia, sediment particles stop following the trails of water elements during the flow passage of a centrifugal pump. In a dredge pump, deviation characteristics of sediment particles from surrounding fluid are still not crystal clear. Apparently, the deviation makes sediment particles attacking the inner wall and causes wear and tear. In addition, the deviation would also decrease the pump efficiency. In order to understand the motion of the sediment particles and their deviation characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In fact, centrifugal methods have been widely used for a number of granular-related experiments. Examples include the centrifuge-based dehydration [15], dredge pumping [16], soil characterization [17], silo discharging [18], surface deformation [19], cohesion measurement [20,21], and mechanical characterization [22][23][24]. In general, centrifuge is useful to separate, transport and deform various materials.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, centrifugal methods have been widely used for a number of granular-related experiments. Examples include the centrifuge-based dehydration [15], dredge pumping [16], soil characterization [17], silo discharging [18], surface deformation [19], cohesion measurement [20,21], and mechanical characterization [22][23][24]. In general, centrifuge is useful to separate, transport and deform various materials.…”
Section: Introductionmentioning
confidence: 99%
“…Adnan et al [21] predicted the wear of lime slurry on slurry pump and found that the cochlear tongue and abdomen of the volute were the most severely worn areas, and the wear rate was proportional to the particle impact rate, particle concentration and particle size. Hong et al [22] proposed a numerical simulation model of a particle motion balance equation based on the particle deposition movement of the pump and found that when the particle movement trajectory in the pump was similar to the blade profile, the particle wear on the blade was very low. Numerical simulation cannot completely predict wear, so some scholars also conducted wear experiments in order to obtain more realistic wear data.…”
Section: Research On Wear Of Solid-liquid Two-phase Centrifugal Pumpmentioning
confidence: 99%
“…The effective depth, inscribed circle diameter, and default rotation speed of the drum of parallel spindle finishing machine are 600 mm, 700 mm, and 30 r/min, respectively. Spherical brown corundum media with the diameter of 3 mm, density of 2675 kgÁm 23 , and load of 60 % were used in the experiment. Two sensors with type LK-G85 and LK-G155 (Keyence Company) were used in the CCD laser displacement sensor system, and the specific parameters are listed in Table 1.…”
Section: Test Platform and Principlementioning
confidence: 99%
“…It can be seen that more researches abroad have been done on the rule of media motion during the vibratory finishing, and less during the spindle finishing. In China, the velocity measurement of small-size particles is mostly applied to multiphase flow of solid, liquid, and gas, [21][22][23][24] while the media velocity is mostly concentrated on theoretical analysis and simulation study in the mass finishing process. 1,3 SM Ji and collegues 25,26 established a Johnson-Cook elastoplastic material model combining the machining mechanism of abrasive flow finishing and studied the relation between the media impact velocity and the abrasion loss, impact times and wear rate, and further proposed an improved soft abrasive flow finishing method.…”
Section: Introductionmentioning
confidence: 99%